Evaluating learning spaces in flood risk management in Germany: Lessons for governance research - Antje Witting; Frederik Brandenstein; Elisa Kochskämper (Journal of Flood Risk Management, 2021)
Efforts to collaboratively manage the risk of flooding are ultimately based on individuals learning about risks, the decision process, and the effectiveness of decisions made in prior situations. This article argues that much can be learned about a governance setting by explicitly evaluating the relationships through which influential individuals and their immediate contacts receive and send information to one another. We define these individuals as "brokers," and the networks that emerge from their interactions as "learning spaces." The aim of this article is to develop strategies to identify and evaluate the properties of a broker's learning space that are indicative of a collaborative flood risk management arrangement. The first part of this article introduces a set of indicators, and presents strategies to employ this list so as to systematically identify brokers, and compare their learning spaces. The second part outlines the lessons from an evaluation that explored cases in two distinct flood risk management settings in Germany. The results show differences in the observed brokers' learning spaces. The contacts and interactions of the broker in Baden-Württemberg imply a collaborative setting. In contrast, learning space of the broker in North Rhine-Westphalia lacks the same level of diversity and polycentricity.
Keywords: 320; brokerage; collaborative water governance; comanagement; comparative analysis; social networks